The Testing of Hall’s Permanent Income Hypothesis: A Case Study of Iran - Yazdan, Gudarzi Farahani; Sina, Merabirad (Asian Economic and Financial Review, 2013)
The objective of this study is to test the Hall’s permanent income hypothesis for Iran using cointegration and error correction model from annual data covering the period of 1980-2010 using annual data from 1980 to 2010. The basic model of permanent income hypothesis showed the validity of absolute income hypothesis while the Campbell and Mankiw (1990) consumption model suggested that the proportion of forward looking consumers in total population is 34 percent and the remaining consumers are backward looking. Therefore in Iran, there is larger fluctuation in per capita income and small opportunity for consumption smoothing.